MATHEMATICS LEARNING DIFFICULTIES OF SLOW LEARNER STUDENTS IN TERMS OF REFLEKTIF ABSTRACTION MEASUREMENT - Risnina Wafiqoh; Said Akhmad Maulana; Surya Amami Pramuditya (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Slow learner students cannot be seen physically, because there is no difference between slow learner students and normal students. Slow learner students must get special attention, especially if the student is a prospective teacher. Slow learner students have difficulties in the process, but the learning difficulties are not in accordance with the facts. This article aims to determine the learning difficulties of slow learners in terms of students' reflective abstractions. The research was conducted using qualitative methods with phenomenological methods. The study involved 8 slow learner students who were given a test to measure their reflective abstraction ability. Followed by interviews based on the results of the written test. The results of the research conducted were analyzed qualitatively. The results of tests and interviews, it is known that students' learning difficulties based on reflective abstraction measurements, are difficulties in remembering mathematical concepts, difficulties in mathematical reasoning, difficulties in providing mathematical explanations, difficulties based on mathematical problem solving strategies, time management difficulties, mathematical technical difficulties, and difficulties in understanding mathematical problems.Siswa slow learner tidak dapat dilihat secara fisik, karena tidak ada perbedaan siswa slow learner degan siswa yang normal. Siswa slow learner tentunya harus mendapatkan perhatian yang khusus, terutama jika siswa tersebut merupakan calon guru. Siswa slow learner memiliki keuslitan-kesulitan dalam proses pembelajaran matematis, namun kesulitan tersebut belum teridentifikasi sesuai dengan fakta di lapangan. Artikel bertujuan untuk mengetahui kesulitan belajar siswa slow learner ditinjau dari abstraksi reflektif siswa. Penelitian dilakukan dengan menggunakan metode kualitatif dengan metode fenomenology. Penelitian melibatkan 8 orang siswa slow learner yang diberikan tes untuk mengukur kemampuan abstraksi reflektif mereka. Dilanjutkan dengan wawancara berdasarkan hasil tes tertulis tersebut. Hasil penelitian dilakukan analisis secara kualitatif. Berdasarkan hasil tes dan wawancara, diketahui kesulitan belajar siswa ditinjau dari pengukuran abstraksi reflektif, adalah kesulitan mengingat konsep matematis, kesulitan bernalar matematis, kesulitan memberikan penjelasan matematis, kesulitan mengatur strategi penyelesaian masalah matematis, kesulitan manajemen waktu, kesulitan teknis matematis, dan kesulitan memahami masalah matematis.